Method for determining iridium content in iridium and iridium alloy
Patent Information
- Application Number
- CN202611082235.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-21
AI Technical Summary
铱及铱合金难熔、难溶解、难加工,现有铱含量检测方法存在溶解效率低、杂质干扰大、精度不足等瓶颈,无法满足材料研发、生产质控的精准需求
在本申请的技术方案中,通过2500℃-2600℃的超高温熔解技术突破现有熔解技术的温度限制,实现铱基样品的快速、彻底熔解,提高熔解效率;利用基体分离技术去除重金属铜、铅、锌、铁、钴、镍、锰,贵金属金、银、铂、钯以及其他难溶金属铑、钌的干扰,提升检测的稳定性;结合耐盐检测技术解决高盐度基体盐析效应、焰色反应、化学干扰、光谱干扰的技术问题,实现高盐基体直接测定,提升检测的稳定性和重复性;采用标准加入法与基体匹配技术消除基体效应,解决基体干扰与化学干扰,实现耐盐性与检测稳定性的协同提升,进一步提升检测的精密度、准确性。
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention relates to the field of precious metal detection technology, specifically to a method for determining the iridium content in iridium and iridium alloys. Background Technology
[0002] Iridium is a platinum group metal with extremely high chemical stability and a melting point as high as 2446℃. Due to its high melting point, high hardness, good corrosion resistance, and excellent catalytic properties, it is almost uncorroded by concentrated acids such as aqua regia at room temperature. When alloyed with platinum, rhodium, rhenium, etc., it can significantly improve corrosion resistance, wear resistance, and creep resistance, making it an irreplaceable special material for extreme environments. Iridium and iridium alloys are difficult to melt, dissolve, and process. Existing methods for detecting iridium content suffer from bottlenecks such as low dissolution efficiency, significant interference from impurities, and insufficient precision, failing to meet the precise requirements of material research and development and production quality control.
[0003] Among the existing detection methods, the pretreatment methods mainly include the following three categories: (1) Alkali fusion method, thiourea enrichment method, assay enrichment method, solvent extraction method, chemical precipitation method and other enrichment and separation methods. Since the melting point of iridium is as high as 2446℃, and the maximum temperature of traditional heating methods such as box-type resistance furnace and muffle furnace is difficult to reach 1400℃, they cannot effectively melt iridium and iridium alloy samples. There are problems such as low melting efficiency, incomplete melting, and disconnection between melting steps and detection steps, resulting in low detection results; (2) Sealed tube chlorination method, which has safety risks. Chlorine is highly toxic and easy to leak; the closed high temperature and high pressure can easily cause the sealed tube to burst; for blocky Iridium, rhodium, ruthenium and other refractory platinum group metals have slow dissolution rates and incomplete dissolution, and are still prone to leaving insoluble residues; the process of sealing, heating, cooling and opening the tube is long, and only one sample can be digested at a time, which is not suitable for batch sample processing; after opening the tube, chlorine gas needs to be specially absorbed, the process is complicated, and the repeatability and reproducibility are poor; (3) High temperature and high pressure closed tank digestion method, the inner liner of the digestion tank is mostly made of polytetrafluoroethylene, which cannot withstand high temperature digestion, and the dense iridium, rhodium and other materials are not completely dissolved; high temperature and high pressure are easily explosive tanks, which have high safety risks; the inner wall of the tank is easily corroded, which can easily introduce impurities and interfere with the measurement; heating and cooling take a long time, the batch efficiency is low, and the parallelism and reproducibility of the results are poor. In the determination stage, atomic absorption spectrometry (AAS), inductively coupled plasma atomic emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), and chemical titration are commonly used for content determination. However, due to the cumbersome pretreatment procedures and the introduction of large amounts of inorganic or organic reagents, chemical interference, spectral interference, mass spectrometry interference, and matrix interference easily occur, resulting in poor stability and low accuracy of the results. The nebulizers used in inductively coupled plasma atomic emission spectrometry are mostly conventional straight-through or shallow-groove structures, and are mostly made of glass or ordinary fluoroplastics. They have two major drawbacks: first, poor salt resistance; for high-salt-concentration iridium-containing test solutions, salt crystal deposition easily clogs the nebulization channel, leading to nebulization interruption and detection signal drift; second, low nebulization efficiency; high-salt iridium-containing test solutions have high viscosity, and conventional nebulizers struggle to form a uniform aerosol, resulting in high relative detection deviation and poor repeatability, failing to meet the high-precision requirements of iridium detection.
[0004] Therefore, developing a method for detecting iridium content in various iridium-based samples, such as iridium and iridium alloys, precious metal iridium alloys, and iridium-containing electronic waste, that is easy to operate, dissolves completely, has minimal interference from impurities, and has high detection accuracy, has become an urgent technical problem to be solved. Summary of the Invention
[0005] In view of the technical problems existing in the background art, this application provides a method for determining the iridium content in iridium and iridium alloys. The method includes sample pretreatment, ultra-high temperature melting at 2500℃-2600℃, matrix separation, leaching and volume adjustment, matrix matching calibration, standard addition method, and salt tolerance testing. Complete melting of iridium is achieved through an ultra-high temperature environment of 2500℃-2600℃; interfering impurities are removed using matrix separation technology; matrix effects are eliminated using the standard addition method and matrix matching technology, thereby improving detection stability; and salt tolerance testing technology is combined to solve the technical problems of salting out effect, flame test, chemical interference, and spectral interference in high-salinity matrices, enabling direct determination of high-salinity matrices and improving detection accuracy. This invention is applicable to the detection of iridium content in various iridium-based samples, including iridium and iridium alloys, iridium-containing precious metal alloys, and iridium-containing electronic waste. It can be widely used in analytical testing, industrial production quality control, and comprehensive utilization of precious metals, and has significant strategic importance for promoting the localization of high-end iridium and iridium alloy materials.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for determining the iridium content in iridium and iridium alloys, comprising: The sample to be tested is pretreated to obtain the matrix; The matrix was immersed in aqua regia for initial separation to obtain a crude purified matrix. The crude purified matrix was mixed with anhydrous chloride salt, evacuated to less than or equal to 5 Pa, and then filled with protective gas to 0.1 MPa-0.2 MPa. The mixture was then melted at 2500℃-2600℃ to obtain a compound containing soluble iridium. The compound containing soluble iridium is immersed in a leaching agent for secondary separation to obtain an iridium-containing test solution; The iridium content was determined by combining the standard addition method with salt tolerance detection technology in the test solution. The mass ratio of the matrix to the anhydrous chloride salt is 1:(6-8); The leaching agents include hydrochloric acid solution and hydrogen peroxide solution.
[0007] Furthermore, the protective gas includes at least one of argon and helium.
[0008] Furthermore, anhydrous chloride salts include at least one of anhydrous sodium chloride, anhydrous potassium chloride, and anhydrous lithium chloride.
[0009] Further, the steps of evacuating the crude purified matrix to a vacuum of less than or equal to 5 Pa, then purging it with a protective gas to 0.1 MPa-0.2 MPa, and melting it at 2500℃-2600℃ to obtain a compound containing soluble iridium include: The crude purified matrix was subjected to a gradient heating at a rate of 45℃ / min-50℃ / min to 2500℃-2600℃ in a protective gas atmosphere of 0.1MPa-0.2MPa to obtain a molten matrix. The molten matrix was cooled to 1000℃-1200℃ at a rate of 28℃ / min-32℃ / min, and then oxygen was introduced and kept at that temperature for 30min-60min to obtain the oxidation-chlorination product. The partial pressure of oxygen was 0.20Pa-0.80Pa. The oxidation-chlorination product was cooled to below 30°C to obtain a compound containing soluble iridium.
[0010] Furthermore, the leaching agents include hydrochloric acid solution and hydrogen peroxide solution, with a volume ratio of hydrochloric acid solution to hydrogen peroxide solution of (4-6):1, a mass fraction of 36%-38% for hydrochloric acid solution, and a mass fraction of 25%-35% for hydrogen peroxide solution.
[0011] Furthermore, the solid-liquid ratio of the matrix to the leachate is (0.25-1) g: 100 mL.
[0012] Furthermore, the steps for determining the iridium-containing test solution using the standard addition method combined with salt tolerance testing technology include: Take several portions of the sample solution to be tested with equal volumes, add different known amounts of iridium standard solution to each portion, and dilute to the same volume with leaching agent to obtain a series of standard solutions to be tested; A series of standards were added to the test solution using a peristaltic pump and sequentially pumped into a salt-resistant V-groove nebulizer to form an aerosol, which was then sent to an inductively coupled plasma atomic emission spectrometer to measure the characteristic signal intensity of iridium in each solution.
[0013] Furthermore, the peristaltic pump operates at a speed of 8-12 rpm, and the atomizing pressure of the salt-resistant V-groove atomizer is 160 kPa-190 kPa.
[0014] Furthermore, the power of the inductively coupled plasma atomic emission spectrometer is 1400W-1500W, the cooling gas flow rate of the salt-resistant V-groove atomizer is 14L / min-15L / min, the signal integration is started after a delay of 30s-50s, the integration time is 25s-35s, and the observation method is radial observation.
[0015] Furthermore, the atomizing gas in the salt-resistant V-groove atomizer is pre-humidified, the temperature of the atomization chamber of the salt-resistant V-groove atomizer is controlled at 30℃-40℃, and the salt-resistant V-groove atomizer is intermittently rinsed with dilute hydrochloric acid with a mass fraction of 5%-10%.
[0016] The beneficial effects of this application are as follows: In the technical solution of this application, the temperature limitations of existing melting technologies are overcome by using ultra-high temperature melting technology at 2500℃-2600℃, achieving rapid and complete melting of iridium-based samples and improving melting efficiency. Matrix separation technology is used to remove interference from heavy metals such as copper, lead, zinc, iron, cobalt, nickel, and manganese, precious metals such as gold, silver, platinum, and palladium, and other sparingly soluble metals such as rhodium and ruthenium, improving detection stability. Salt tolerance detection technology is combined to solve the technical problems of salting-out effect, flame reaction, chemical interference, and spectral interference in high-salinity matrices, enabling direct determination of high-salinity matrices and improving detection stability and repeatability. The standard addition method and matrix matching technology are used to eliminate matrix effects, solve matrix interference and chemical interference, and achieve a synergistic improvement in salt tolerance and detection stability, further enhancing the precision and accuracy of the detection.
[0017] The above description is merely an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Detailed Implementation
[0018] The following embodiments are only used to illustrate the technical solutions of this application more clearly, and are therefore only examples and should not be used to limit the scope of protection of this application.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion.
[0020] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0021] In the description of the embodiments of this application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or positional relationship are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on the embodiments of this application.
[0022] Iridium is a platinum group metal with extremely high chemical stability and a melting point as high as 2446℃. Due to its high melting point, high hardness, good corrosion resistance, and excellent catalytic properties, it is almost uncorroded by concentrated acids such as aqua regia at room temperature. When alloyed with platinum, rhodium, rhenium, etc., it can significantly improve corrosion resistance, wear resistance, and creep resistance, making it an irreplaceable special material for extreme environments. Iridium and iridium alloys are difficult to melt, dissolve, and process. Existing methods for detecting iridium content suffer from bottlenecks such as low dissolution efficiency, significant interference from impurities, and insufficient precision, failing to meet the precise requirements of material research and development and production quality control.
[0023] Among the existing detection methods, the pretreatment methods mainly include the following three categories: (1) Alkali fusion method, thiourea enrichment method, reagent enrichment method, solvent extraction method, chemical precipitation method and other enrichment and separation methods. Due to the high melting point of iridium (2446℃), when metallic iridium and high-melting-point iridium alloys are present, the maximum heating temperature by traditional heating methods (box resistance furnace, muffle furnace) is generally no more than 1400℃, which cannot effectively melt iridium and iridium alloy samples. There are problems such as low melting efficiency, incomplete melting, and disconnection between melting steps and detection steps, resulting in low detection results; (2) Sealed tube chlorination method, which has safety risks, chlorine is highly toxic and leaks easily; sealed high temperature and high pressure are prone to This can lead to the sealing tube bursting; the dissolution rate of refractory platinum group metals such as iridium, rhodium, and ruthenium is slow and incomplete; it is easy to leave insoluble substances; the process of sealing, heating, cooling, and opening the tube is long, and only one sample can be digested at a time, which is not suitable for batch sample processing; chlorine gas needs to be specially absorbed after opening the tube; the process is complicated and has poor repeatability and reproducibility; (3) High temperature and high pressure closed tank digestion method: the inner liner of the digestion tank is mostly made of polytetrafluoroethylene, which cannot withstand high temperature digestion and does not completely dissolve dense iridium, rhodium, etc.; the high temperature and high pressure explosion tank has a high safety risk; the inner wall of the tank is easy to corrode and easily introduces impurities, which interferes with the measurement; heating and cooling take a long time, the batch efficiency is low, and the parallelism and reproducibility of the results are poor. In the determination stage, atomic absorption spectrometry (AAS), inductively coupled plasma atomic emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), and chemical titration are commonly used for content determination. However, due to the cumbersome pretreatment procedures and the introduction of large amounts of inorganic or organic reagents, chemical, spectral, mass spectrometric, and matrix interferences occur, resulting in poor stability and low accuracy of the results. The nebulizers used in inductively coupled plasma atomic emission spectrometry are mostly conventional straight-through or shallow-groove structures, and are mostly made of glass or ordinary fluoroplastics. They have two major drawbacks: first, poor salt resistance; for high-salt-concentration iridium-containing test solutions, salt crystallization and deposition easily clog the nebulization channel, leading to nebulization interruption and detection signal drift; second, low nebulization efficiency; high-salt iridium-containing test solutions have high viscosity, and conventional nebulizers struggle to form a uniform aerosol, resulting in high relative deviation and poor repeatability, failing to meet the high-precision requirements of iridium detection. Therefore, developing a method for detecting iridium content in various iridium-based samples, such as iridium and iridium alloys, precious metal iridium alloys, and iridium-containing electronic waste, that is easy to operate, dissolves completely, has minimal interference from impurities, and has high detection accuracy, has become an urgent technical problem to be solved.
[0024] To address the aforementioned problems, in a first aspect, the present invention proposes a method for determining the iridium content in iridium and iridium alloys, comprising: The sample to be tested is pretreated to obtain the matrix; The matrix was immersed in aqua regia for initial separation to obtain a crude purified matrix. The crude purified matrix was mixed with anhydrous chloride salt, evacuated to less than or equal to 5 Pa, and then filled with protective gas to 0.1 MPa-0.2 MPa. The mixture was then melted at 2500℃-2600℃ to obtain a compound containing soluble iridium. The compound containing soluble iridium is immersed in a leaching agent for secondary separation to obtain an iridium-containing test solution; The iridium content was determined by combining the standard addition method with salt tolerance detection technology in the test solution. The mass ratio of the matrix to the anhydrous chloride salt is 1:(6-8); The leaching agents include hydrochloric acid solution and hydrogen peroxide solution.
[0025] In the technical solution of this application, "iridium" in "iridium and iridium alloys" refers to crude iridium that has not been refined or purified. Pretreatment of the test samples includes processing the iridium and iridium alloy test samples into powder or fragments with a particle size of less than or equal to 150 μm using mechanical crushing, grinding, or other methods to increase the contact area with various reagents and improve cleaning efficiency. The samples are then soaked in alcohol for 20 minutes to remove surface oil. Additionally, for test samples with an oxide layer on the surface, they can be soaked in 5%-10% dilute hydrochloric acid for 5-10 minutes, followed by repeated rinsing with pure water 3-5 times to remove the surface oxide layer and residual impurities, thus improving the cleaning efficiency. The treated test samples are then placed in an oven and dried at 105℃ for 2 hours until constant weight is achieved. The resulting matrix is then placed in a desiccator for later use to remove volatile moisture and reduce potential oxidation caused by moisture and systematic errors due to differences in water content.
[0026] Further, the matrix is immersed in aqua regia for initial separation, including weighing 0.5g-2.0g of the matrix, adding 100mL of aqua regia (a mixed solution of concentrated hydrochloric acid and concentrated nitric acid in a volume ratio of 3:1), and heating at 200℃-250℃ until no bubbles are generated. At this time, copper, lead, zinc, iron, cobalt, nickel, manganese, and precious metals gold, silver, platinum, and palladium in the matrix dissolve into the solution in the form of chloride ion complexes. The soluble metals in the matrix undergo the following reactions: M + HNO3 + HCl → H n [MCl m ]+NO↑+H2O M represents all soluble matrix metals (such as Cu, Pb, Zn, Fe, Co, Ni, Mn, Au, Ag, Pt, Pd), H n [MCl m[] indicates the soluble chloride complex ion of the corresponding metal (such as H[AuCl4], H2[PtCl6], H[CuCl4]). Iridium, rhodium, and ruthenium in the matrix are highly chemically inert and difficult to oxidize and coordinate, remaining as elements or oxides. Vacuum filtration using an organic filter membrane with a pore size of 0.45 μm is employed to obtain elemental iridium, rhodium, and ruthenium or their oxides, achieving initial separation of the matrix. The beaker and precipitate are rinsed 4-6 times to obtain a crude purified matrix, reducing impurity interference and improving the detection purity of iridium.
[0027] Furthermore, iridium has a high melting point of 2446℃ and extremely strong chemical stability. Starting a vacuum induction melting furnace can provide temperatures higher than iridium's melting point, breaking through this limitation and completely melting the crude purified matrix, thus disrupting its stable crystal structure and facilitating subsequent digestion. The system is then evacuated to a vacuum of 5 Pa or less to reduce gaseous impurities, followed by the introduction of a protective gas with a purity higher than 99.999% to 0.1 MPa-0.2 MPa, forming an inert protective atmosphere. Iridium and iridium alloys undergo chlorination under ultra-high temperature and inert gas protection conditions. The inert protective atmosphere reduces the oxygen partial pressure within the system, inhibiting the oxidation of iridium to insoluble oxides such as Ir₂O₃ and IrO₂, thereby improving the selectivity of the chlorination reaction. The mass ratio of the matrix to anhydrous chloride is controlled at 1:(6-8). Within this range, the anhydrous chloride is sufficient to provide enough chlorine to form soluble iridium compounds IrCl4 and a small amount of IrCl3 during the melting process of the crude purified matrix. This promotes the complete digestion of iridium and iridium alloys and improves the accuracy of subsequent iridium content detection.
[0028] Iridium reacts with anhydrous chlorides under ultra-high temperature and argon protection conditions to undergo an oxidative chlorination reaction, producing iridium tetrachloride as the main product. 4; Under conditions involving trace amounts of oxygen, a side reaction occurs to produce a small amount of iridium trichloride: .
[0029] The generated iridium tetrachloride and iridium trichloride are soluble iridium compounds, which are used for subsequent iridium determination.
[0030] Further, the iridium-containing compound was immersed in a leaching agent for secondary separation to obtain an iridium-containing test solution. The leaching agent included hydrochloric acid solution and hydrogen peroxide solution. The iridium-containing compound was then removed, pulverized to a particle size of less than 100 μm, placed in a 250 mL beaker, and the leaching agent was added. The mixture was heated at 200℃-250℃ for 2-3 hours to completely dissolve the iridium-containing compound. Iridium was then separated into hexachloroiridium(III) ions ([IrCl6)). 3- ) and hexachloroiridium(IV) ion ([IrCl6] 2- It exists in solution in the form of iridium(IV) hexachloro[IrCl6].2- When in contact with water in an acidic environment, it is readily reduced to iridium(III) hexachloro[IrCl6] ion. 3- This further hydrolyzes to form insoluble IrO2, leading to iridium loss. Hydrogen peroxide, as a strong oxidizing agent, re-oxidizes trivalent iridium to tetravalent iridium, increasing the concentration of hexachloroiridium(IV) ion [IrCl6] in the iridium-containing test solution. 2- The stability of [IrCl6] is determined by the presence of concentrated hydrochloric acid, which provides hydrogen and chloride ions. Hydrogen ions maintain a strongly acidic environment, while chloride ions, through common ion effects and coordination equilibrium, inhibit [IrCl6]. 2- Hydrolysis and substitution of coordinated water molecules stabilize the complex. After cooling to below 30°C, the precipitate is removed by filtration with medium-speed filter paper. The filtrate is transferred to a 100 mL volumetric flask, and the beaker and filter paper are rinsed 3-5 times with hydrochloric acid. The rinsing solution is then transferred to the volumetric flask, and the solution is brought to the mark and shaken well to obtain the iridium-containing test solution.
[0031] Furthermore, the iridium-containing test solution was analyzed using a standard addition method combined with salt tolerance detection technology to determine the iridium content. The standard addition method, based on the Lambert-Beer law, involves adding a known amount of iridium standard solution to the test solution, plotting a signal intensity-standard addition curve, and then using an extrapolation method to determine the iridium concentration in the test solution. This eliminates interference from residual impurities in the sample and errors caused by instrument drift (such as fluctuations in nebulization efficiency and spectral signal shift). Accurate quantification of iridium in complex matrix samples can be achieved without separating all matrix impurities, further improving detection accuracy. In this application, the iridium-containing test solution contains a high concentration of chloride. The salt tolerance detection technology refers to the use of ICP-OES to analyze iridium-containing test solutions by setting appropriate key parameters for the nebulizer and peristaltic pump to achieve continuous and stable nebulization of the test solution containing a high concentration of chloride, reducing nozzle clogging and enabling direct injection analysis of iridium-containing test solutions with salt concentrations as high as 20%-30%. The use of salt-resistant detection technology inhibits salt precipitation and deposition, ensuring continuous atomization and stable signal baseline. On the other hand, it improves the atomization uniformity of high-salt iridium-containing test solutions, making aerosol generation more stable and controllable, improving detection repeatability, and thus enhancing the detection accuracy of iridium-containing test solutions.
[0032] In some embodiments, the protective gas includes at least one of argon and helium.
[0033] In this embodiment, the protective gas includes at least one of argon and helium. Argon has a higher density than air and settles on the surface of the melt, forming a gas covering layer that physically isolates oxygen. Argon has low thermal conductivity, which reduces heat loss from the melt, maintains temperature stability, and keeps costs under control. Helium has the same inertness as argon and can also suppress the oxidation of iridium during ultra-high temperature melting.
[0034] In some embodiments, the anhydrous chloride salt includes at least one of anhydrous sodium chloride, anhydrous potassium chloride, and anhydrous lithium chloride.
[0035] In this embodiment, the anhydrous chloride salt includes at least one of anhydrous sodium chloride, anhydrous potassium chloride, and anhydrous lithium chloride. Anhydrous lithium chloride reacts with iridium to form soluble lithium chloroiridate, which has strong digestion ability and can dissolve the insoluble iridium phase. Anhydrous potassium chloride effectively disrupts the matrix lattice of silicates, aluminates, etc., which encapsulate iridium, and reduces the melt viscosity, promoting ion diffusion and mass transfer, and accelerating the reaction process. Anhydrous lithium chloride can also provide a chlorine source and is low in cost, and can be used as the basis for eutectic mixtures in combination with other anhydrous chloride salts.
[0036] In some embodiments, the step of evacuating the crude purified matrix to a vacuum of less than or equal to 5 Pa, then purging it with a protective gas to 0.1 MPa-0.2 MPa, and melting it at 2500℃-2600℃ to obtain a compound containing soluble iridium includes: The crude purified matrix was subjected to a gradient heating at a rate of 45℃ / min-50℃ / min to 2500℃-2600℃ in a protective gas atmosphere of 0.1MPa-0.2MPa to obtain a molten matrix. The molten matrix is cooled to 1000℃-1200℃ at a rate of 28-32℃ / min, and then oxygen is introduced and kept at this temperature for 30min-60min to obtain an oxidation-chlorination product with a partial pressure of oxygen of 0.20Pa-0.80Pa. The oxidation-chlorination product was cooled to below 30°C to obtain a compound containing soluble iridium.
[0037] In this embodiment, the crude purified matrix is heated to 2500℃-2600℃ at a gradient rate of 45℃ / min-50℃ / min and then held at that temperature for 5min-10min to disrupt the crystal structure of the iridium and iridium alloy samples, allowing them to melt completely and facilitating the digestion of iridium. The trace oxygen in the ultra-high temperature environment of 2500℃-2600℃ will oxidize iridium, generating volatile IrO3 gaseous oxide, causing iridium to be lost with the flue gas and reducing the recovery rate. Cooling the melted matrix to 1000℃-1200℃ at a rate of 28-32℃ / min and then introducing trace oxygen significantly reduces the volatility of the iridium oxide. Maintaining a trace oxygen atmosphere during the 30min-60min holding period allows for material locking while simultaneously initiating the target oxidation-chlorination reaction under the influence of trace oxygen: in the oxidation reaction, iridium is oxidized to a tetravalent oxide: Ir + O2 → IrO2; subsequently, chlorination coordination occurs, and the tetravalent iridium oxide reacts with Cl provided by the molten chloride salt. - Coordination produces soluble sodium hexachloroiridium(IV)ate: IrO2 + 6NaCl + 2Cl2 → Na2IrCl6 + 2Na2O. After dissolving in hydrochloric acid, it can dissociate to release IrCl4, a soluble chloroiridium salt, which is convenient for subsequent determination.
[0038] In some embodiments, the leaching agent includes hydrochloric acid solution and hydrogen peroxide solution, wherein the volume ratio of hydrochloric acid solution to hydrogen peroxide solution is (4-6):1, the mass fraction of hydrochloric acid solution is 36%-38%, and the mass fraction of hydrogen peroxide solution is 25%-35%.
[0039] In this embodiment, the leaching agent is a mixture of 36%-38% hydrochloric acid solution and 25%-35% hydrogen peroxide solution at a volume ratio of (4-6):1. When the soluble sodium hexachloroiridium(IV)ate generated during digestion comes into contact with the mixture of concentrated hydrochloric acid and hydrogen peroxide, it dissociates and dissolves, forming hexachloroiridium(IV)ate [IrCl6]. 2- Na₂IrCl₆→2Na + +IrCl6 2- Ir(IV) hexachloroiridium(IV) ion [IrCl6] 2- When in contact with water in an acidic environment, it is readily reduced to iridium(III) hexachloro[IrCl6] ion. 3- This further hydrolyzes to form insoluble IrO2, leading to iridium loss. Hydrogen peroxide, as a strong oxidizing agent, re-oxidizes trivalent iridium to tetravalent iridium, increasing the concentration of hexachloroiridium(IV) ion [IrCl6] in the iridium-containing test solution. 2- The stability of [IrCl6] is improved. At this volume ratio, concentrated hydrochloric acid provides a high concentration of hydrogen and chloride ions, which inhibits the hexachloroiridium(IV) ion [IrCl6]. 2- Hydrolysis of iridium is prevented, maintaining its tetravalent chloride complex form and reducing hydrolysis losses. The addition of hydrogen peroxide promotes rapid oxidation of trivalent iridium and maintains a continuous oxidizing atmosphere to preserve the tetravalent state of iridium, thereby increasing the leached hexachloroiridium(IV) ion [IrCl6]. 2- Stability.
[0040] In some embodiments, the solid-liquid ratio of the matrix to the leachate is (0.25-1) g: 100 mL.
[0041] In this embodiment, the solid-liquid ratio of the matrix to the leaching agent is controlled at (0.25-1) g: 100 mL. After initial separation and melting, the matrix yields a compound containing soluble iridium. This solid-liquid ratio provides sufficient leaching agent to submerge the compound containing soluble iridium, promoting the dissolution of soluble iridium and increasing the leaching rate. Simultaneously, this range allows control of the concentration of the iridium-containing test solution within the measurement range of the instrument, improving the accuracy of the measurement results.
[0042] In some embodiments, the steps of determining the iridium-containing test solution using a standard addition method combined with salt tolerance testing technology include: Take several portions of the sample solution to be tested with equal volumes, add different known amounts of iridium standard solution to each portion, and dilute to the same volume with leaching agent to obtain a series of standard solutions to be tested; A series of standards were added to the test solution using a peristaltic pump and sequentially pumped into a salt-resistant V-groove nebulizer to form an aerosol, which was then sent to an inductively coupled plasma atomic emission spectrometer to measure the characteristic signal intensity of iridium in each solution.
[0043] In this embodiment, the iridium content is determined using the standard addition method. First, the addition samples are prepared. Four 100mL volumetric flasks are used, and 20mL of the iridium-containing test solution is transferred to each flask. 0mL, 1.0mL, 2.0mL, and 3.0mL of iridium standard solution with a concentration of 100μg / mL are added sequentially. The solution is then diluted to the mark with leaching agent and shaken well to obtain four standard addition samples. Subsequently, the signal intensity of each standard addition sample is measured. A working curve is established with the added concentration as the x-axis and the signal intensity as the y-axis. This working curve is extended backwards to obtain the concentration value at the intersection with the x-axis, i.e., when the signal is at its lowest value. The absolute value of this concentration is taken to obtain the original concentration of iridium in the iridium-containing test solution. This invention uses a salt-resistant V-groove nebulizer, model Thermo Fisher 510-10QDAC, to create a salt-resistant V-groove nebulizer and a method for determining iridium parameters using ICP-OES. After the high-salt iridium-containing test solution containing chloride enters through the injection tube, a uniform liquid film is formed under the guidance of the V-groove. Atomizing gas blows through the bottom of the groove, breaking the liquid film into uniform aerosols with a particle size of 1μm-5μm, meeting the requirements of ICP-OES detection. This achieves continuous and stable atomization of a high-salt iridium chloride system with a mass fraction of 20%-30%. By setting synergistic parameters such as the V-groove structure, low pressure and low pump speed, high-power cooling gas, and heating, humidification, and rinsing, the system achieves both salt resistance and anti-clogging, as well as efficient and uniform atomization, thereby improving the accuracy of iridium content determination. The standard addition method allows the iridium standard solution and the test sample to be measured in the same chemical environment, reducing matrix interference, lowering the relative deviation of the detection, and further improving the precision and stability of iridium detection. This achieves a synergistic improvement in salt resistance, atomization efficiency, and detection stability, solving technical problems such as salting-out effect, flame reaction, chemical interference, and spectral interference in ultra-high salinity matrices. It enables direct determination of high-salt concentration matrices, meeting the needs of high-precision analysis.
[0044] In some embodiments, the peristaltic pump rotates at 8 rpm to 12 rpm, and the atomizing pressure of the salt-resistant V-groove atomizer is 160 kPa to 190 kPa.
[0045] In this embodiment, the peristaltic pump speed is controlled at 8-12 rpm, and the atomizing gas pressure of the salt-resistant V-groove atomizer is 160 kPa-190 kPa. This reduces the liquid film tearing speed and minimizes channel blockage caused by salt crystal nucleation within the V-groove, enabling tolerance to high-salt iridium-containing test solutions with a mass fraction of 20%-30%. By setting a low-pressure, low-pump-speed anti-clogging parameter system, rapid chloride crystallization is inhibited, thus improving salt tolerance.
[0046] In some embodiments, the radio frequency power of the inductively coupled plasma atomic emission spectrometer is 1400W-1500W, the cooling gas flow rate of the salt-resistant V-groove atomizer is 14L / min-15L / min, the signal integration is started after a delay of 30s-50s, the integration time is 25s-35s, and the observation method is radial observation.
[0047] In this embodiment, the radio frequency (RF) power of the inductively coupled plasma optical emission spectrometer is set to 1400W-1500W, the cooling gas flow rate of the salt-resistant V-groove nebulizer is set to 14L / min-15L / min, and the observation method is radial observation. RF power within this range enhances plasma stability, resists matrix effects, and suppresses signal drift. Cooling gas flow rate within this range enhances cooling, reduces torch temperature, and thus reduces salt molten adhesion to the walls. Radial observation reduces axial signal interference and self-absorption caused by high-salt iridium-containing analytes. The combined effect of these three factors reduces the sensitivity of chemical and ionization interference to power fluctuations, improves the plasma's resistance to high-salt matrix interference, reduces signal drift, and improves measurement accuracy. Since the high-salt iridium-containing analyte in the system has high viscosity and slow atomization transmission, the salt needs time to establish a stable state at the central tube opening. A stabilization delay of 30s-50s is initially set to allow the sample aerosol to reach concentration equilibrium in the plasma. After the signal stabilizes, signal integration begins, which improves the accuracy of iridium content determination. An integration time of 25s-35s is beneficial for stabilizing readings. By extending the integration time, signal fluctuations caused by high salt content can be offset, improving the consistency of repeated measurements and thus enhancing the accuracy of the measurement.
[0048] In some embodiments, the atomizing gas in the salt-resistant V-groove atomizer is pre-humidified, the temperature of the atomization chamber of the salt-resistant V-groove atomizer is controlled at 30°C-40°C, and the V-groove atomizer is intermittently rinsed with dilute hydrochloric acid with a mass fraction of 5%-10%.
[0049] In this embodiment, the atomizing gas in the salt-resistant V-groove atomizer is pre-humidified, and the temperature of the atomization chamber of the salt-resistant V-groove atomizer is controlled at 30℃-40℃. This maintains the humidity and temperature at the nozzle, inhibiting the rapid crystallization of chlorides. Iridium in the digested test solution is [IrCl6]. 3- [IrCl6] 2-The presence of chloride complexes and iridium complexes, which exhibit metal adsorption properties, may lead to complexation and deposition in the sample inlet tubing, the inner wall of the V-groove nebulizer, and the surface of the mist chamber, interfering with the detection of the next set of samples. Rinsing between samples with 5%-10% hydrochloric acid for 60 seconds, followed by rinsing with water for 60 seconds, is compatible with the chloride salt system used in the initial digestion and can specifically dissolve Ir-Cl complexes and crystals such as NaCl and CaCl2 without requiring disassembly and cleaning. By setting anti-crystallization process parameters, crystal residue can be reduced while improving measurement efficiency.
[0050] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0051] I. Preparation Method Example 1 The iridium alloy sample to be tested was selected as No. 1. The sample was ground into powder with a particle size of 150 μm. After soaking in alcohol for 20 min, it was soaked in dilute hydrochloric acid with a volume concentration of 5% for 5 min. It was rinsed repeatedly with pure water 3 times. The treated sample was placed in an oven and dried at 105℃ for 2 h. After drying to constant weight, it was taken out to obtain the matrix, which was placed in a desiccator for later use. Weigh 1.0g of the above matrix, add 100mL of aqua regia and heat at 200℃ until no bubbles are generated. Use a 0.45um organic filter membrane for vacuum filtration, rinse the beaker and precipitate 5 times to obtain the crude purified matrix. Anhydrous chloride was weighed according to a matrix-to-anhydrous chloride mass ratio of 1:6. The anhydrous chloride was obtained by mixing anhydrous potassium chloride and anhydrous lithium chloride in a 1:1 mass ratio. The crude purified matrix and anhydrous chloride were mixed and placed in a pure tungsten crucible. The crucible was placed in the center of the vacuum induction melting furnace cavity. The furnace door was closed, and the vacuum pump was started to evacuate the furnace cavity to 5 Pa. Then, high-purity argon gas (≥99.999%) was introduced to 0.15 MPa. The vacuum induction melting furnace was started, and the temperature was first increased to 2500℃ at a rate of 50℃ / min and held for 8 min. Then, the temperature was decreased to 1100℃ at a rate of 30℃ / min, oxygen was introduced, and the partial pressure of oxygen was controlled at 0.40 Pa. The temperature was held for 45 min, and then cooled to 30℃. The crucible was removed, yielding a compound containing soluble iridium. The soluble iridium compound was extracted and pulverized to a particle size of 100 μm using an agate mortar. The pulverized compound was placed in a 250 mL beaker, and a mixture of 36% hydrochloric acid and 30% hydrogen peroxide (prepared at a volume ratio of 5:1) was added. The mixture was heated at 200 °C for 2.5 h, cooled to 30 °C, and filtered through medium-speed filter paper to remove the precipitate. The filtrate was transferred to a 100 mL volumetric flask, and the beaker and filter paper were rinsed four times with hydrochloric acid. The rinsing solution was transferred to the volumetric flask as well, and the solution was brought to the mark and shaken well to obtain the iridium-containing test solution.
[0052] Take four 100mL volumetric flasks, transfer 20mL of iridium-containing test solution to each flask, and then add 0mL, 1.0mL, 2.0mL and 3.0mL of iridium standard solution with a concentration of 100μg / mL in sequence. Dilute to the mark with a mixture of concentrated hydrochloric acid and 30% hydrogen peroxide with a volume ratio of 5:1, shake well, and obtain four standard samples.
[0053] Use an inductively coupled plasma optical emission spectrometer (ICP-OES instrument) equipped with a salt-resistant V-groove atomizer and set the following parameters: Radio frequency power: 1450W, nebulizing gas pressure: 180kPa, peristaltic pump speed: 10rpm, cooling gas flow rate: 15L / min, auxiliary gas flow rate: 0.7L / min, nebulization chamber temperature: 35℃, argon humidification: carrier gas humidified with warm water, integration time: 30s stabilization after sample injection followed by 30s integration, observation height: 12mm, detection wavelength: 212.681nm, sample intervals were rinsed with 5% hydrochloric acid for 60s followed by rinsing with water for 60s. The instrument was preheated for 40min after ignition. Iridium standards were injected in ascending order of concentration. The net emission intensity of each standard-added sample solution was collected at the selected wavelength.
[0054] Plot a standard curve with the concentration of added iridium standard on the x-axis and the detection signal intensity on the y-axis. The intersection of the curve's extrapolation with the x-axis represents the concentration of iridium in the iridium-containing test solution. Calculate the iridium mass fraction (ω) using the following formula: In the formula: ω represents the mass fraction of iridium (%). c represents the concentration of iridium in the iridium-containing test solution (μg / mL). V1 is the total volume of the iridium-containing test solution (100 mL). m is the mass (g) of the sample to be tested.
[0055] The iridium content of Example 1 was obtained by taking the average value of seven parallel determinations and retaining the result to two decimal places.
[0056] Example 2 Unlike Example 1, the mass ratio of the matrix to anhydrous chloride was 1:7. The measurements were performed in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. This yielded the iridium content of Example 2.
[0057] Example 3 Unlike Example 1, the mass ratio of the matrix to anhydrous chloride was 1:8. The measurements were performed in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be repeated here. This yielded the iridium content of Example 3.
[0058] Example 4 Unlike Example 1, sample #2 was selected for testing. The test was performed in parallel for 7 times and the average value was taken to obtain the iridium content of Example 4.
[0059] Example 5 Unlike Example 1, sample #3 was selected for testing. The test was performed in parallel for 7 times and the average value was taken to obtain the iridium content of Example 5.
[0060] Example 6 Unlike Example 1, sample #4 was selected for testing. The test was performed in parallel for 7 times and the average value was taken to obtain the iridium content of Example 6.
[0061] Example 7 Unlike Example 1, sample #5 was selected for testing. The test was performed in parallel for 7 times and the average value was taken to obtain the iridium content of Example 7.
[0062] Example 8 Unlike Example 1, sample #6 was selected for testing. The test was performed in parallel for 7 times and the average value was taken to obtain the iridium content of Example 8.
[0063] Example 9 Unlike Example 1, the peristaltic pump rotated at 8 rpm, and the average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be described in detail here. This yielded the iridium content of Example 9.
[0064] Example 10 Unlike Example 1, the peristaltic pump rotated at 12 rpm, and the average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be repeated here. This yielded the iridium content of Example 10.
[0065] Example 11 Unlike Example 1, the atomizing pressure of the salt-resistant V-groove atomizer was 160 kPa. The average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be repeated here. The iridium content of Example 11 was obtained.
[0066] Example 12 Unlike Example 1, the atomizing pressure of the salt-resistant V-groove atomizer was 190 kPa. The average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be repeated here. The iridium content of Example 12 was obtained.
[0067] Example 13 Unlike Example 1, the cooling gas flow rate of the salt-resistant V-groove atomizer was 14 L / min. The average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be repeated here. The iridium content of Example 13 was obtained.
[0068] Example 14 Unlike Example 1, the integration time was 25 seconds, and the average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be described in detail here. This yielded the determined iridium content of Example 14.
[0069] Example 15 Unlike Example 1, the integration time was 35 seconds, and the average value was taken from three parallel measurements. The remaining steps were roughly the same and will not be described in detail here. This yielded the determined iridium content of Example 15.
[0070] Example 16 Unlike Example 1, the salt-resistant V-groove atomizer was intermittently rinsed with 10% hydrochloric acid by mass, and the average value was taken after three parallel measurements. The remaining steps were roughly the same and will not be described in detail here. This yielded the iridium content of Example 16.
[0071] Comparative Example 1 Unlike Example 1, the mass ratio of the matrix to anhydrous chloride was 1:3. The measurements were performed in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. This yielded the determination of the iridium content in Comparative Example 1.
[0072] Comparative Example 2 Unlike Example 1, the mass ratio of the matrix to anhydrous chloride was 1:4. The measurements were performed in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. This yielded the determination of iridium content in Comparative Example 2.
[0073] Comparative Example 3 Unlike Example 1, the mass ratio of the matrix to anhydrous chloride was 1:5. The measurements were performed in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. This yielded the determination of the iridium content in Comparative Example 3.
[0074] Comparative Example 4 Unlike Example 1, the leaching agent was replaced by a 36% hydrochloric acid solution instead of a mixture of hydrochloric acid and hydrogen peroxide. The results were measured in three parallel measurements and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. The iridium content of Comparative Example 4 was obtained.
[0075] Comparative Example 5 Unlike Example 1, the leaching agent was replaced by aqua regia instead of a mixture of hydrochloric acid and hydrogen peroxide. The results were measured in three parallel measurements and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. The iridium content of Comparative Example 5 was obtained.
[0076] Comparative Example 6 Unlike Example 1, the leaching agent was replaced by a mixture of hydrochloric acid and hydrogen peroxide, which was prepared in a volume ratio of 5:1 with a mixture of 36% hydrochloric acid and 3% sodium chlorate. The results were measured in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. The iridium content of Comparative Example 6 was obtained.
[0077] Comparative Example 7 Unlike Example 1, the leaching agent was replaced by a mixture of hydrochloric acid and hydrogen peroxide, which was prepared in a volume ratio of 5:1 with a mixture of 3% thiourea and 30% hydrogen peroxide. The results were measured in three parallel trials and the average value was taken. The remaining steps were roughly the same and will not be described in detail here. The iridium content of Comparative Example 7 was obtained.
[0078] Comparative Example 8 Conventional nebulizers prioritize high atomization efficiency, employing high atomizing gas pressures (220kPa-260kPa) and high pump speeds (15rpm-20rpm). However, in high-salt conditions, this can lead to excessively fine droplets and rapid salt precipitation, causing blockage and signal drift, resulting in a surge in precision and a decrease in measurement accuracy. Salt-resistant V-groove nebulizers, on the other hand, prioritize stability, anti-clogging, and salt resistance, using low atomizing gas pressures (160kPa-190kPa) and low pump speeds (10rpm-12rpm). In high-salt conditions, this results in moderate droplet size, slow evaporation, reduced crystallization, and a stable signal, thus reducing precision and improving measurement accuracy. A comparison of parameters and optimization parameters between conventional and salt-resistant V-groove nebulizers is shown in Table 1.
[0079] Table 1. Atomizer Parameters and Optimization Comparison Unlike Example 1, a common nebulizer was used for the determination. Based on the parameters set in Table 1 (RF power 1200W, nebulizing gas pressure 220kPa, injection rate 18rpm, integration time 10s, room temperature nebulization, no intermittent rinsing), the test sample 1# was tested. Five parallel determinations were performed to obtain the iridium content of Comparative Example 8.
[0080] Comparative Example 9 Unlike Example 1, the digestion process used conventional sealed-tube chlorination (the sealed-tube chlorination digestion method in Appendix A of YS / T371-2006) instead of ultra-high temperature melting; the determination process used conventional calibration instead of standard addition, i.e., the iridium standard solution was directly diluted stepwise with deionized water to prepare a series of calibration standard solutions of known concentrations, without adding any other elements or matrix components. However, the same salt-resistant V-groove nebulizer and ICP-OES instrument parameters as in Example 1 were still used to determine the iridium content of the sample 1# to be tested. Five independent parallel determinations were performed to obtain the iridium content of Comparative Example 9.
[0081] II. Testing Methods The test sample numbered #1 in Example 1 was derived from the standard sample numbered HJ-35; The test sample numbered #2 in Example 4 was derived from the standard sample numbered HJ-34; The test sample numbered #3 in Example 5 was derived from the standard sample numbered HJ-36; The test sample numbered #4 in Example 6 was derived from the standard sample numbered HJ-37; The test sample numbered #5 in Example 7 was derived from the standard sample numbered HJ-38; The test sample numbered #6 in Example 8 was taken from the standard sample numbered HJ-39.
[0082] In addition, the test samples used in Examples 2-3, Examples 9-16 and Comparative Examples 1-9 were the same as those used in Example 1, and the standard values of iridium content in the standard samples are shown in Table 2.
[0083] Table 2. Composition of Experimental Samples Note: -- indicates not detected, or the content is below the method detection limit.
[0084] The iridium content was determined using the corresponding methods described above: The vacuum melting furnace used for melting is model KDH-500ES; The salt-resistant V-groove atomizer is model Thermo Fisher 510-10QDAC; The inductively coupled plasma atomic emission spectrometer is a Thermo Fisher ICAP7600. The test environment was 24℃ and 64% humidity.
[0085] III. Analysis of Test Results for Each Embodiment and Comparative Example Table 3 shows the measurement results of Examples 1-3 and Comparative Examples 1-3. Table 4 shows the measurement results of Examples 1 and 4-8. Table 5 shows the measurement results of Examples 9-16. Table 6 shows the measurement results of Example 1 and Comparative Examples 4-7. Table 7 compares the usage of ordinary atomizers and salt-resistant V-groove atomizers. Results analysis: In Example 1, sample 1# was measured 7 times. To facilitate comparison with other examples and comparative examples, the data from the first 3 measurements of Example 1 were used in Tables 3 and 6. In the results analysis of Comparative Examples 8 and 9, the data from the first 5 measurements of Example 1 were used. The iridium content was expressed as mass fraction (%). RSD is the relative standard deviation, which measures the precision of the measurement results.
[0086] As shown in Table 3, in Comparative Examples 1-3, the mass ratio of the test sample to anhydrous chloride was less than 1:6. Due to insufficient addition of anhydrous chloride, sufficient chlorine could not be provided during the melting process to form a soluble iridium compound, IrCl4, resulting in a low degree of iridium and iridium alloy digestion and a low iridium content determination result. When the mass ratio was 1:(6-8), the iridium content determination result was close to the standard value and met the detection requirements.
[0087] As shown in Table 4, the precision and accuracy of the iridium content measured in Examples 2-8 using the same method as in Example 1 for samples with different iridium contents meet the detection requirements.
[0088] Table 5 shows that Examples 9-16 adjusted the process parameters of inductively coupled plasma atomic emission spectrometry (ICP-AES) and measured the same samples as in Example 1. The average value of the measured results was 5.21%-5.24%, and the RSD was 0.11%-0.66%. The precision and accuracy of the measured iridium content met the detection requirements. When the peristaltic pump speed was in the range of 8-12 rpm, the volume of liquid to be tested delivered to the nebulizer per unit time could maintain a sufficient supply of liquid film inside the nebulization chamber. When the nebulizing gas pressure was 160-190 kPa, the kinetic energy of the argon gas was sufficient to tear the high-salt iridium chloride liquid into uniform fine aerosols, which entered the plasma excitation zone, maintaining the effective excitation concentration and spectral response signal of iridium in the plasma, suppressing signal fluctuation amplitude, and improving detection precision. When the cooling gas flow rate of the nebulizer was 14-15 L / min, the cooling gas flow rate could maintain a constant operating temperature of the nebulization chamber and the plasma torch, stabilizing the iridium excitation efficiency and spectral signal, and controlling batch detection errors. By controlling the integration time to 25-35 seconds, the detector can completely acquire the characteristic light signal emitted by iridium, suppressing transient aerosol concentration fluctuations within the plasma, reducing the volatility of parallel sample detection results, and improving detection precision. Simultaneously, it reduces the wear and tear on core components such as the detector, RF generator, and peristaltic pump caused by the long integration time, ensuring stable equipment operation. A sufficient chloride ion concentration of 5%-10% (by mass) in dilute hydrochloric acid allows for reversible ligand displacement between chloride ions and iridium ions adsorbed on the tube wall, converting the solid-state adsorbed [IrCl6] into a liquid form. 3- [IrCl6] 2- It is converted back into soluble chloride complex ions and completely discharged with the rinsing waste liquid, reducing interference with subsequent sample determination.
[0089] Table 6 shows that in Comparative Example 4, only hydrochloric acid was used as the leaching agent. Due to the weak oxidizing power of hydrochloric acid, the leaching ability was poor, resulting in a lower iridium content determination. In Comparative Example 5, aqua regia was used as the leaching agent. The introduction of nitric acid complicated the system, leading to a lower iridium content determination. In Comparative Example 6, the hydrochloric acid + sodium chlorate system introduced a large amount of sodium salt, causing severe matrix and spectral interference during the determination. In Comparative Example 7, the efficiency of the complexation reaction between thiourea and iridium in the thiourea + hydrogen peroxide system was low, resulting in a lower iridium content determination. In summary, hydrochloric acid + hydrogen peroxide is the most ideal leaching agent. Under the action of the strong oxidant hydrogen peroxide, the leaching effect of iridium is the best, while avoiding the introduction of too many salts. Because Ir is the third transition series, its d orbital is contracted, the ligand exchange rate is extremely slow, and it can exist stably in solution for a long time. It is not easily hydrolyzed or replaced by other ligands. Iridium is leached with hexachloroiridium(III) ion [IrCl6]. 3- And hexachloroiridium(IV) ion [IrCl6] 2- It exists in solution.
[0090] In Comparative Example 8, the ordinary atomizer began to clog after the third measurement, with an average iridium content of 6.56% and an RSD of 14.42%. Example 1 used a salt-resistant V-groove atomizer, combined with salt resistance detection technology, and measured an average iridium content of 5.28% with an RSD of 0.90%, differing from the standard value of 5.26% by 0.02%. After 25 consecutive measurements, the salt-resistant V-groove atomizer still showed no clogging, the detection signal drift was 0.8% within 2 hours, and no salt crystal deposition was observed in the atomization channel. The statistical results of all examples are shown in Table 7.
[0091] In Comparative Example 9, the average iridium content was 4.83%, with an RSD of 4.89%, a difference of 0.43% from the standard value of 5.26%, indicating poor precision due to the large RSD. The digestion and determination time for Comparative Example 9 was greater than 24 hours, while the procedure in Example 1 took approximately 3 hours, a time consumption of more than eight times. Using the method of this patent, the same sample was independently measured five times in parallel, yielding an average iridium content of 5.28% with an RSD of 0.90%, a difference of 0.02% from the standard value of 5.26%. The determination method of this application significantly improves precision and accuracy compared to the conventional sealed-tube chlorination method described above.
[0092] In summary, this invention significantly improves the digestion efficiency and detection accuracy of various iridium-based samples, including iridium and iridium alloys, by using ultra-high temperature melting technology combined with matrix separation, matrix matching, standard addition method, and salt resistance detection technology. It solves many bottlenecks of existing technologies, is easy to operate, has wide applicability, and has high practicality and promotion value.
[0093] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for determining the iridium content in iridium and iridium alloys, characterized in that, include: The sample to be tested is pretreated to obtain the matrix; The matrix was immersed in aqua regia for initial separation to obtain a crude purified matrix. The crude purified matrix is mixed with anhydrous chloride salt, evacuated to less than or equal to 5 Pa, and then filled with protective gas to 0.1 MPa-0.2 MPa. The temperature is then increased to 2500℃-2600℃ at a gradient rate of 45℃ / min-50℃ / min and held for 5min-10min to obtain the molten matrix. The molten matrix is cooled to 1000℃-1200℃ at a rate of 28℃ / min-32℃ / min, and then oxygen is introduced and kept at that temperature for 30min-60min to obtain an oxidation-chlorination product, wherein the partial pressure of the oxygen is 0.20Pa-0.80Pa. The oxidation-chlorination product was cooled to below 30°C to obtain a compound containing soluble iridium; The soluble iridium compound was immersed in a leaching agent for secondary separation to obtain an iridium-containing test solution; The iridium-containing test solution was analyzed using a standard addition method combined with salt tolerance detection technology to determine the iridium content. The mass ratio of the matrix to the anhydrous chloride is 1:(6-8); The leaching agent includes hydrochloric acid solution and hydrogen peroxide solution.
2. The method for determining the iridium content in iridium and iridium alloys according to claim 1, characterized in that, The protective gas includes at least one of argon and helium.
3. The method for determining the iridium content in iridium and iridium alloys according to claim 1, characterized in that, The anhydrous chloride salt includes at least one of anhydrous sodium chloride, anhydrous potassium chloride, and anhydrous lithium chloride.
4. The method for determining the iridium content in iridium and iridium alloys according to claim 1, characterized in that, The volume ratio of the hydrochloric acid solution to the hydrogen peroxide solution is (4-6):1, the mass fraction of the hydrochloric acid solution is 36%-38%, and the mass fraction of the hydrogen peroxide solution is 25%-35%.
5. The method for determining the iridium content in iridium and iridium alloys according to claim 1, characterized in that, The solid-liquid ratio of the matrix to the leachate is (0.25-1) g: 100 mL.
6. The method for determining the iridium content in iridium and iridium alloys according to claim 1, characterized in that, The steps for determining the iridium-containing test solution using the standard addition method combined with salt tolerance testing technology include: Take several portions of the sample solution to be tested with equal volumes, add different known amounts of iridium standard solution to each portion, and dilute to the same volume with the leaching agent to obtain a series of standard solutions to be tested; The series of standards were added to the test solution using a peristaltic pump and sequentially pumped into a salt-resistant V-groove nebulizer to form an aerosol, which was then sent to an inductively coupled plasma atomic emission spectrometer to measure the characteristic signal intensity of iridium in each solution.
7. The method for determining the iridium content in iridium and iridium alloys according to claim 6, characterized in that, The peristaltic pump rotates at 8 rpm to 12 rpm, and the atomizing pressure of the salt-resistant V-groove atomizer is 160 kPa to 190 kPa.
8. The method for determining the iridium content in iridium and iridium alloys according to claim 6, characterized in that, The radio frequency power of the inductively coupled plasma atomic emission spectrometer is 1400W-1500W, the cooling gas flow rate of the salt-resistant V-groove atomizer is 14L / min-15L / min, the signal integration is started after a delay of 30s-50s, the integration time is 25s-35s, and the observation method is radial observation.
9. The method for determining the iridium content in iridium and iridium alloys according to claim 6, characterized in that, The atomizing gas in the salt-resistant V-groove atomizer is pre-humidified, the temperature of the atomization chamber of the salt-resistant V-groove atomizer is controlled at 30℃-40℃, and the salt-resistant V-groove atomizer is intermittently rinsed with dilute hydrochloric acid with a mass fraction of 5%-10%.
Citation Information
Patent Citations
Method used for rapid measuring of content of iridium in iridium-containing material
CN109115567A
Detection method of niobium and tantalum
CN115032262A